In office external bleaching of teeth with discoloration: a case report - Anindya, Cinitra; Ismiyatin, Kun; Zubaidah, Nanik; Supandji, Rafaelle Raditya; Nurkhalidah, Binar Najwa (Conservative Dentistry Journal, 2024)
Background: Tooth discoloration is a prevalent issue that significantly impacts an individual's self-confidence. Fortunately, dentists offer highly effective and non-invasive teeth whitening techniques that use higher concentrations of hydrogen peroxide (HP) of around 35% to 40%. These techniques can help resolve the problem of teeth discoloration better than at-home methods designed to deliver faster results. This is particularly helpful when immediate whitening is required. Purpose: This case study aims to report cases of in-office external bleaching of discolored teeth. Case: A 29-year-old woman complained about the yellowish shade of her teeth, which made her feel less confident due to the yellowish color. Case Management: The management for discoloration of teeth was done with dental bleaching using 40% hydrogen peroxide. As a result of the treatment, the desired tooth color increased from 3M1 to 1M1 Vita 3D Master and from Opalescence no.6 to 4. Conclusion: In-office dental bleaching is a highly effective treatment option for correcting tooth discoloration that dental professionals widely use. The procedure can significantly improve the appearance of discolored teeth and increase self-confidence of the patient.